2012
DOI: 10.1002/macp.201200332
|View full text |Cite
|
Sign up to set email alerts
|

Plant Oil‐Based Long‐Chain C26 Monomers and Their Polymers

Abstract: The self‐metathesis of erucic acid with ruthenium‐based catalysts, followed by the hydrogenation of the double bond, yielded 1,26‐hexacosanedioic acid (AA). Polycondensation of this biobased long‐chain α,ω‐dicarboxylic acid with hexacosane‐1,26‐diol (BB), generated from the former by reduction, yielded the polyester 26,26. Monomer AA was also polymerized with short‐chain alkanediols, namely dodecane‐1,12‐diol and butane‐1,4‐diol, generating polyesters 12,26 and 4,26, respectively. The properties of these aliph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 47 publications
1
82
0
Order By: Relevance
“…Long chain aliphatic polyesters prepared by polycondensation of monomers obtained from 10-undecenoic acid and erucic acid. 26,27 By following the same strategy, erucic acid [(Z)-docos-13-enoic acid], a monounsaturated fatty acid readily available from rapeseed or cramble oils, was converted into a 1,26-diacid and diol. 27 These two monomers were polycondensed yielding a polyester 26,26 with a molecular weight of 14 kg mol −1 (Scheme 5).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Long chain aliphatic polyesters prepared by polycondensation of monomers obtained from 10-undecenoic acid and erucic acid. 26,27 By following the same strategy, erucic acid [(Z)-docos-13-enoic acid], a monounsaturated fatty acid readily available from rapeseed or cramble oils, was converted into a 1,26-diacid and diol. 27 These two monomers were polycondensed yielding a polyester 26,26 with a molecular weight of 14 kg mol −1 (Scheme 5).…”
Section: Methodsmentioning
confidence: 99%
“…26,27 By following the same strategy, erucic acid [(Z)-docos-13-enoic acid], a monounsaturated fatty acid readily available from rapeseed or cramble oils, was converted into a 1,26-diacid and diol. 27 These two monomers were polycondensed yielding a polyester 26,26 with a molecular weight of 14 kg mol −1 (Scheme 5). This polyester showed a melting transition at 104 °C with a temperature corresponding to 5 wt% degradation equal to 386 °C.…”
Section: Methodsmentioning
confidence: 99%
“…BC membranes have also been used as nanostructured substrates for the preparation of luminescent bio-based materials because of their singular morphology and mechanical properties. 41,42 Specifically, Caiut et al 41 prepared luminescent BC composite membranes by the incorporation of ethanolic solutions of different europium compounds, namely, [Eu(4,4,4-trifluoro-1-phenyl-1,3-butanedione) 3 2 ], into the BC network followed by drying. The obtained membranes were semitransparent, self-sustainable, and showed strong emission under UV excitation.…”
Section: Reviewmentioning
confidence: 99%
“…Indomethacin presented a fast-release profile, whereas doxorubicin showed sustained release behavior. Furthermore, the upconversion NPs luminescent intensity ratios of 2 115 Although in these cases, we are not dealing specifically with materials where gelatin plays the role of a matrix in a nanocomposite material, this approach might be quite promising notable to improve the biocompatibility of such particles, while retaining the core optical properties in biomedical applications, namely, in the imaging field. Finally, gelatin has also been used as starting material for the hydrothermal preparation of highly fluorescent carbon QDs.…”
Section: Gelatinmentioning
confidence: 99%
“…However, the chemical process is also of potential interest. It does not rely on an oxidative process, but is instead based on redistribution of the olefinic bonds of unsaturated fatty acids via a self-metathesis reaction (Behr et al, 2014;Chikkali and Mecking, 2012;Jenkins et al, 2015;Levin et al, 2015;Meier, 2000;Montero de Espinosa and Meier, 2012;More et al, 2013;Ngo and Foglia, 2009;Nicolaou et al, 2005;Ohlmann et al, 2012;Ozturk et al, 2015;Le Ravalec et al, 2010;Tomasek and Schatz, 2013;Vilela et al, 2012;Vyshnavi et al, 2013;Wels et al, 2013;Winkler and Meier, 2014). For example, Foglia has shown that 1,18-octadec-9-enedioic acid (2) can be obtained with a yield of 71% from oleic acid (1) if it is stirred mechanically at 45…”
Section: Introductionmentioning
confidence: 99%